DEVELOPMENT OF THE AIR BANGIS BEACH TOURIST AREA IN SUNGAI BEREMAS SUB-DISTRICT, WEST PASAMAN REGENCY - Hayati, Risda; Yumarni, Yumarni; Milantara, Noril (Sylva Jurnal Ilmu-ilmu Kehutanan, 2024)
An area that is a tourist attraction must have uniqueness which is the main target when visiting the tourist area. This research aims to determine the development of the Air Bangis Beach tourist area in Sungai Beremas District, West Pasaman Regency. The research was carried out by direct observation using questionnaires with SWOT analysis. Data analysis through strategic planning methods is used to evaluate strengths, weaknesses, opportunities and threats that occur in a project or in a business venture, or evaluate one's own product lines or those of competitors. To carry out the analysis, the business objectives are determined or the objects to be analyzed are identified. Strengths and weaknesses are grouped into internal factors, while opportunities and threats are identified as external factors. The research results show that tourist attractions that have good potential need to develop ecotourism to obtain various benefits for socio-economic, socio-cultural, flora and fauna.